If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying R + 4 = 12 Reorder the terms: 4 + R = 12 Solving 4 + R = 12 Solving for variable 'R'. Move all terms containing R to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + R = 12 + -4 Combine like terms: 4 + -4 = 0 0 + R = 12 + -4 R = 12 + -4 Combine like terms: 12 + -4 = 8 R = 8 Simplifying R = 8
| 6n+45=4n-15 | | f(x+4)=8(x+4)-2 | | (8+z)(5z+9)=0 | | -2-3x+5=16+2x+22 | | .75x=.51 | | 8.5x-12=6.5x-18 | | (4z+5)(4+z)=0 | | 27y^3+36y^2+12y= | | y=6x^2+7x-10 | | 8.5x-12=6.5-18 | | 6-2x+8y+4x-15y= | | 1-t+2.2t=5.9 | | m^2+10m+41=0 | | 0.5(x+6)+1.5(x-5)= | | z^2-20=0 | | 3(1+h)=3h-9 | | 7y^2+12y=0 | | .8x=43 | | 3s^3-16s+5= | | 2x^2+4x+5=x | | -6y^2+53y+9= | | -.22x=.4 | | 32.31+31.32x=41.89 | | 2log^3x=log^3(x+6) | | 1.25x=3.75 | | 2xsquared+8=0 | | -10x^2+79x+8= | | 4x^2-28x+13=0 | | k*3(x-12)-3x=12 | | -7(m)=-42 | | P=a+b+4csolving | | p(5)=10-2q |